Application of Space Technologies Aimed at Proprioceptive Correction in Terrestrial Medicine in Russia - Motanova, Eugenia; Bekreneva, Maria; Rukavishnikov, Ilya; Shigueva, Tatiana A.; Saveko, Alina A.; Tomilovskaya, Elena S. (Frontiers in Physiology, 2022)
Space technologies greatly contributed not only to space medicine but also to terrestrial medicine, which actively involves these technologies in everyday practice. Based on the existing countermeasures, and due to similarities of sensorimotor alterations provoked by weightlessness with various neurological disorders, a lot of work has been dedicated to adaptation and introduction of these countermeasures for rehabilitation of patients. Axial loading suit and mechanical stimulation of the soles’ support zones are used in mitigation of stroke and traumatic brain injury consequences. They are also applied for rehabilitation of children with cerebral palsy. Complex application of these proprioceptive correction methods in neurorehabilitation programs makes it possible to effectively treat neurological patients with severe motor disturbances and significant brain damage.